Simulation of smallholder farming systems in the Olifants river basin, South Africa - (:unkn) unknown (My University, 2008)
Smallholder farming systems are characterized by low yields and high risks of crop failure threatening family food security. A farming systems simulation model, OLYMPE to understand and improve the existing farming practices for 10 years is presented in semi-arid Olifants river basin, South Africa. The OLYMPE model has a socio-economic analysis component to explore farmer income subject to constraints of capital, land, water availability, labour, and market price dynamics. Five farming systems types were identified from surveys and later discussed with farmers and extension officers for validation. It was found that farm types with high livestock units were the most resilient, followed by farm types with crop diversification to climatic and market shocks. However, extreme events such as cyclone affected all the farm types at different levels. Returns to labour ranged from 0 to ZAR 7646/person, with the highest under Type E followed by Type C with ZAR 1822/person. OLYMPE model was able to simulate the farming systems productions with good performance in the catchment. The results indicate that livestock and crop diversification are most adept strategies to ensure stable income and food security to the smallholder farmers. Hence, technology innovations and policies should articulate solutions to poor yields based on these two aspects.
Keywords: African Research